Pulmonary arterial hypertension associated with congenital heart disease: lessons learnt from the large Turkish Nationwide Registry (THALES). (June 2021) - Kücükoglu, Serdar M.; Kaymaz, Cihangir; Alehan, Dursun; Kula, Serdar; Akcevin, Atıf; Celiker, Alpay; Cicek, Sertac M.; Tokgözoglu, Lale S.; Kentli, Suleyman; ,
Pulmonary hypertension is a group of diseases, including pulmonary arterial hypertension associated with congenital heart disease (APAH-CHD), characterized by progressive deterioration in pulmonary hemodynamics associated with substantial morbidity and mortality risk. THALES is a national multicenter, prospective observational registry, providing data on patients with APAH-CHD. The study comprised APAH-CHD patients (>3 months of age) with confirmed diagnosis of right heart catheterization or echocardiographic findings. Initial and follow-up data were collected via regular hospital visits. Descriptive statistics are used for definitive purposes. Overall, 1034 patients aged 3 months–79 years (median 11.2 [Q1–Q3: 2.2–24.3] years) with APAH-CHD were enrolled at 61 centers, 50.3% being retrospectively enrolled. Most had either Eisenmenger's syndrome (49.2%) or systemic-to-pulmonary shunts (42.7%). Patients were mostly in functional class I–II at the time of diagnosis (46.6%). Mean 6-min walk distance (6MWD) was 369 ± 120 m. Mean pulmonary arterial pressure was 54.7 ± 22.2 mmHg for the whole group, and was highest in patients with Eisenmenger's syndrome. Targeted therapies were noted in 398 (38.5%) patients (monotherapy in 80.4%). Follow-up data were available in 506 patients. Survival at 140 months was 79% and was associated with baseline 6MWD >440 m ( p  = 0.009), brain natriuretic peptide level < 300 ng/L ( p  < 0.001). Follow-up 6MWD >165 m ( p  < 0.0001), brain natriuretic peptide level <300 ng/L ( p  = 0.031), and targeted therapies ( p  = 0.004) were also predictive of survival. THALES is the largest registry dedicated to APAH-CHD to date and provides important contributions on demographics, clinical characteristics, and gaps in disease management.